2001
DOI: 10.1080/095371001317126383
|View full text |Cite
|
Sign up to set email alerts
|

Description of 10 new mutations in platelet glycoprotein IIb (αIIb) and glycoprotein IIIa (β3) genes

Abstract: In this study we have used denaturing gradient gel electrophoresis (DGGE) for identifying sequence alterations in glycoprotein (GP) IIb and IIIa genes from 20 patients affected by Glanzmann's thrombasthenia. These patients were from 16 different families. Using computer modelling, we divided the promoters, coding sequences and flanking splicing regions, in 31 segments for the GPIIb gene and 19 domains for the GPIIIa gene. We were able to find a mutation potentially affecting GPIIb-IIIa expression or function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…So far, four clusters of affected families have been reported Rosenberg et al, 1997;Vinciguerra et al, 2000], including one in southern India [Khanduri et al, 1981]. Molecular genetic studies revealed that separate founder mutations account for GT in most Iraqi Jewish patients in Israel [Rosenberg et al, 1997;Thornton et al, 1999], most Palestinian Arabs [Thornton et al, 1999;Rosenberg et al, 2005], and French gypsies [Vinciguerra et al, 2000]. The present study indicates that the southern Indian ''cluster'' of GT patients is characterized by a great variety of mutations, among which only two or three founder mutations were discerned in 17 of the 40 families examined.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…So far, four clusters of affected families have been reported Rosenberg et al, 1997;Vinciguerra et al, 2000], including one in southern India [Khanduri et al, 1981]. Molecular genetic studies revealed that separate founder mutations account for GT in most Iraqi Jewish patients in Israel [Rosenberg et al, 1997;Thornton et al, 1999], most Palestinian Arabs [Thornton et al, 1999;Rosenberg et al, 2005], and French gypsies [Vinciguerra et al, 2000]. The present study indicates that the southern Indian ''cluster'' of GT patients is characterized by a great variety of mutations, among which only two or three founder mutations were discerned in 17 of the 40 families examined.…”
Section: Discussionmentioning
confidence: 95%
“…The first mutation causing GT was described in 1990 ] and since then more than 100 mutations have been reported (http://sinaicentral.mssm.edu/intranet/research/ glanzmann/). Although most mutations are sporadic, founder mutations have been described in highly consanguineous populations, including Iraqi Jews and Arabs living in Israel Rosenberg et al, 1997Rosenberg et al, , 2005 and gypsies living in France [Schlegel et al, 1995;Vinciguerra et al, 2000]. The identification of disease-causing mutations led to the development of assays for carrier testing and prenatal diagnosis [French et al, 1998], revealed different mechanisms of mutagenesis and abnormal gene expression Rosenberg et al, 1997;Schlegel et al, 1995;Li and Bray, 1993;Djaffar et al, 1993;Burk et al, 1991;Jin et al, 1996], and provided important insights into the structure and function of aIIbb3 [French and Seligsohn, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…4A). Moreover, each of the algorithms identified a cluster of three presumptive GT variants with a low probability of being deleterious, and it may be valuable to study these in more detail [αIIb P76A and β3 M321L (64), and H652L (65)]. The concordance between prediction tools for individual variants is displayed as a heat map in Fig.…”
Section: Assessment Of the Effect Of Three Novel Variants On αIibβ3 Ementioning
confidence: 99%
“…10,11 Interestingly, this mutation was detected in all GT patients coming from the Manouche community and originating from different regions of France, the socalled French Gypsy mutation. 12,13 Moreover, this mutation appears limited to this tribe, which led us to hypothesize the existence of a founder mechanism in this population. [14][15][16] In this study, we examined whether GT patients within different families originating from the Manouche tribe and carrying the French Gypsy mutation share a common ancestor, and if so, to estimate the age of the founding event.…”
Section: Introductionmentioning
confidence: 91%